Börjes bravader: Överraskningar och en resa i manlighetens paradoxer - Nilsson, Bo (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2002)
This article is about different meanings of masculinity and "to be surprised". The point of departure is 25 interviews with men living in the countryside of northern Sweden. By creating a "faction" — a story about one man, but built on the compilation of the 25 interviews — I show how masculinity can be constructed during a holiday in a foreign country. The leading character goes through a fateful moment — a beauty contest — and this changes both his relation to the phenomenon "to be surprised" and his way of acting as a man. One reason for this is that he represent a lower class manhood, a protest masculinity.